(untitled) (Experimental biology, 2009)
It is established that mRNA of CDH1 gene of human is been reacted 29 entergenic miRNAs and 15 intronic miRNAs. Value of score and binding free energy between miRNA and 3’-untranslated region of mRNA of CDH1 gene were calculated. Binding particularities of examined miRNAs with this region of mRNA of CDH1 gene were revealed.